Blood flukes exploit Peyer's Patch lymphoid tissue to facilitate transmission from the mammalian host. - Joseph D Turner; Priyanka Narang; Mark C Coles; Adrian P Mountford (PLoS Pathogens)
Schistosomes are blood-dwelling parasitic helminths which produce eggs in order to facilitate transmission. Intestinal schistosomes lay eggs in the mesenteries, however, it is unclear how their eggs escape the vasculature to exit the host. Using a murine model of infection, we reveal that Schistosoma mansoni exploits Peyer's Patches (PP) gut lymphoid tissue as a preferential route of egress for their eggs. Egg deposition is favoured within PP as a result of their more abundant vasculature. Moreover, the presence of eggs causes significant vascular remodeling leading to an expanded venule network. Egg deposition results in a decrease in stromal integrity and lymphoid cellularity, including secretory IgA producing lymphocytes, and the focal recruitment of macrophages. In mice lacking PP, egg excretion is significantly impaired, leading to greater numbers of ova being entrapped in tissues and consequently, exacerbated morbidity. Thus, we demonstrate how schistosomes directly facilitate transmission from the host by targeting lymphoid tissue. For the host, PP-dependency of egg egress represents a trade-off, as limiting potentially life-threatening morbidity is balanced by loss of PP structure and perturbed PP IgA production.